Teaching Critical Thinking in the Language Classroom (Eurasian Research Bulletin, 2023)
Critical thinking refers to the individuals’ ability to think and make correct decisions independently. Nowadays enhancing critical thinking in learners is considered one of the foreign language teachers’ tasks due to its high position in foreign language classrooms. There are various factors affecting language learners’ critical thinking skills. Among these factors is the assessment methods used. Therefore, through managing the ways of assessing language learners' ability, language teachers can help them develop critical thinking skills. In this we will talk about critical thinking and ways to enhance it.